Allocation of Study Time in Chinese Junior School Students: Habitual Responding, Item Difficulty, and Time Constraints - Wang, Fuyun; Qin, Qiwen; Jiang, Yanju (Frontiers in Psychology, 2016)
The present study investigated factors influencing Chinese junior school students’ study time allocation and the age difference in the effect of habitual responding. Participants were 240 junior school students (120 girls, 120 boys; aged 13–15 years) with half taking part in experiment 1 and half in experiment 2, and 240 young adults aged 18-23 years, (120 women and 120 men,) involved in experiment 3a and 3b, all native Chinese speakers. In Experiments 1 and 3a, Chinese word pairs (e.g., moon–star) were presented on the screen with three items in one array. In each trial, the items were arranged from left to right, either easy, moderate, then difficult, or the reverse. Participants had either 5 s or no time limits to study the word pairs. In Experiment 2&3b, word pairs were ordered in a column with the easiest items either at the top or bottom position. Results showed interactions among item difficulty, item order, and time limitation in terms of effects on study time allocation of junior school students. Participants tended to learn the items in order (from left to right and from top to bottom), but the effect of item difficulty was greater than that of item order on item selection. Results indicated that agenda and habitual responding have a combined effect on study time allocation and that the contribution of agenda is greater than that of habitual responding. The effect of habitual responding on the self-paced study and recall performance of junior school students is greater than its effect on young adults, and the study time allocation of junior school students is more likely to be affected by external conditions.